Improving the phylogenetic resolution of Malaysian and Javan mahseer (Cyprinidae), Tor tambroides and Tor tambra: Whole mitogenomes sequencing, phylogeny and potential mitogenome markers - Chung, Hung Hui; Lim, Leonard Whye Kit; Mei, Melinda Lin Lau; Fazimah, Aziz; Han, Ming Gan (Elsevier Inc., 2021)
The true mahseer (Tor spp.) is one of the highest valued fish in the world due to its high nutritional value and great unique taste. Nevertheless, its morphological characterization and single mitochondrial gene phylogeny in the past had yet to resolve the ambiguity in its taxonomical classification. In this study, we sequenced and assembled 11 complete mahseer mitogenomes collected from Java of Indonesia, Pahang and Terengganu of Peninsular Malaysia as well as Sarawak of East Malaysia. The mitogenome evolutionary relationships among closely related Tor spp. samples were investigated based on maximum likelihood phylogenetic tree construction. Compared to the commonly used COX1 gene fragment, the complete COX1, Cytb, ND2, ND4 and ND5 genes appear to be better phylogenetic markers for genetic differentiation at the population level. In addition, a total of six population-specific mitolineage haplotypes were identified among the mahseer samples analyzed, which this offers hints towards its taxonomical landscape.